The Role of Kindergarten Teachers Fostering Play-Based Instruction - Donasco, Elizabeth D.; Vertulfo, Ria M. (Journal of Education and Training, 2024)
Teachers play an important role for the students learning and development. There are varieties of learning strategies on today’s generation which are effective to the student’s development and learning. Fostering a play based learning, especially in kindergarten students is a great learning strategy for all kindergarten teachers. Teachers have an important role incorporating play in the lesson that will make the students have fun while learning, and make it easier way for the teachers to teach the young learners. This study utilized descriptive phenomenological research design as a method to characterize the experiences of the subjects. The study conducted at a pre-school. The participants of the study are those kindergarten teachers who foster already the play-based learning in their classroom, who already have experiences in fostering this kind of learning strategy. Due to the study is using descriptive design, the researchers conducted a face-to-face interview to all the participants of the study that will lasts between 30-40 minutes. The researchers used semi-structured interview in which the questions are open-ended style. The data were utilized using the Collaizi's analysis method to examine the collected data in this study. This strategy enables a thorough investigation, allowing the researchers to develop a comprehensive interpretation of the data and eventually arrive at a dependable result. After a long analysis of the themes of the interview, it summed up with 4 concepts and end of up a general concept which it is called the Constructive Journeying of the kindergarten teachers.. As a result, the constructive journey of the kindergarten teachers is the effective and recommended role that the kindergarten teachers must possess if they foster the play based learning in their discussion. In order to become a great and effective teacher, using the 4 themes to derive a generalized concept, the Constructive Journey. This shall help the teachers to reflect and enhance their teaching ways and develop the learning of the young learners through fostering the play- based learning.